Increased TLR4 pathway activation and cytokine imbalance led to lipopolysaccharide tolerance in monocytes from preeclamptic women - Romao-Veiga, Mariana [UNESP]; Bannwart-Castro, Camila Ferreira [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Golim, Marjorie de Assis [UNESP]; Peracoli, Jose Carlos [UNESP]; Peracoli, Maria Terezinha Serrao [UNESP] (Elsevier B.V., 2020)
Preeclampsia (PE) is a pregnancy syndrome characterized by a systemic inflammatory response, and endogenous activation of monocytes. This study aimed to determine whether the activation of monocytes from preeclamptic women might interfere with the response to lipopolysaccharide (LPS)-in vitro stimulation. Fifty-two preeclamptic women and 32 normotensive (NT) pregnant women were included. Monocytes from peripheral blood were cultured with or without LPS. TLR4 expression was analyzed by flow cytometry, NF-kappa B activity was determined in nuclear extracts and cytokines production was evaluated by ELISA. Endogenous TLR4 ligands such as Hyaluronan, HMGB1 and Hsp70 were determined in plasma. The endogenous TLR4 expression and activation of NF-kappa B were statistically higher in monocytes from women with PE compared to NT group. Early-onset PE showed higher TLR4 expression compared to late-onset PE. Plasma levels of Hyaluronan, HMGB1, and Hsp70, as well as endogenous production of inflammatory cytokines, were elevated whilst lower production of IL-10 was observed in the PE group. After culture with LPS, monocytes presented lower NF-kappa B activation, TNF-alpha and IL-12 production in PE groups than in the NT group. The study demonstrates endogenous activation of monocytes from preeclamptic women, accompanied by higher expression of TLR4, NF-kappa B activation and elevated production of pro-inflammatory cytokines. The higher plasma levels of the TLR4 ligands hyaluronan, HMGB1 and hsp70, as well as the high concentration of TNF-alpha endogenously produced by monocytes, could induce the LPS tolerance phenomenon in these cells. These results suggest that monocytes play an important role in the maternal excessive systemic inflammatory response in PE.
Keywords: Preeclampsia; Monocytes; TLR receptors; LPS tolerance; Cytokines